Cardiac rehabilitation in the elderly patient in eight rehabilitation units in Western Europe: Baseline data from the EU-CaRE multicentre observational study. (July 2019) - Prescott, Eva; Mikkelsen, Nicolai; Holdgaard, Annette; Eser, Prisca; Marcin, Thimo; Wilhelm, Matthias; Gil, Carlos Peña; González-Juanatey, José R; Moatemri, Feriel; Iliou, Marie Christine; Schneider, Steffen; Schromm, Eike; et al.
Background: Due to the progressive deconditioning, comorbidities and higher complication rates, elderly patients are in particular need of cardiac rehabilitation. We compared elderly patients (65+ years old) participating in cardiac rehabilitation, focusing on baseline characteristics, risk factor control and functional assessment. Methods: The EU-CaRE study is a prospective study comparing cardiac rehabilitation in eight centres across Western Europe. Consecutive patients with acute coronary syndrome, stable coronary artery disease and heart valve replacement undergoing cardiac rehabilitation were included. Results: Of1 633 patients (median age 72 years) participating, 54% had acute coronary syndrome, 33% had stable coronary artery disease and 13% followed valve replacement. Fifty-five per cent had undergone percutaneous coronary intervention and 29% coronary artery bypass grafting. Characteristics varied across centres: 23% (17–27%) were women, 4% (0–12%) were of non-European origin and 16% (4–32%) were living alone. Median time from index event to start of cardiac rehabilitation varied from 11 to 49 days ( p  < 0.001). Mean VO2peak was relatively low (16 mL/kg per min) and varied significantly between the participating centres, largely unaffected by multivariable adjustment. Overall patients received guideline recommended treatment: 93% (87–97%) were on a statin and 70% (55–85%) an angiotensin-converting enzyme inhibitor/angiotensin receptor blocker. However, risk factor control was inadequate: 58% had three or more risk factors not controlled. Conclusion: EU-CaRE provides a snapshot of the elderly population with heart disease participating in cardiac rehabilitation across countries in Western Europe. Risk factors and exercise capacity indicate the continued need for cardiac rehabilitation in these patients. Of concern, the lag-time to start of cardiac rehabilitation needs improvement in many centres.